Buy ology : truth and lies about why we buy - Lindstrom, Martin, 1970- (New York : Broadway Books, 2010)
In BUYOLOGY, Lindstrom, who was voted one of Time Magazine's most influential people of 2009, presents the astonishing findings from his groundbreaking, three-year, seven-million-dollar neuromarketing study, a cutting-edge experiment that peered inside the brains of 2,000 volunteers from all around the world as they encountered various ads, logos, commercials, brands, and products. His startling results shatter much of what we have long believed about what seduces our interest and drives us to buy. Filled with entertaining inside stories about how we respond to well-known brands.
A rush of blood to the head : the largest neuromarketing study ever conducted -- This must be the place : product placement, American Idol, and Ford's multimillion dollar mistake -- I'll have what she's having : mirror neurons at work -- I can't see clearly now : subliminal messaging, alive and well -- Do you believe in magic? : ritual, superstition, and why we buy -- I say a little prayer : faith, religion, and brands -- Why did I choose you? : the power of somatic markers -- A sense of wonder : selling to our senses -- And the answer is ... : neuromarketing and predicting the future -- Let's spend the night together : sex in advertising -- Brand new day : the future of marketing and advertising -- Conclusion : good times, bad times.
"With a new chapter on buying in today's economy"--Cover.
Previously published in hardcover in slightly different form: New York : Doubleday, 2008.
Includes bibliographical references (p. 239-243) and index.
Keywords: Neuromarketing; Consumer behavior; Consumers -- Psychology; Shopping -- Psychological aspects; Marketing -- Psychological aspects